Anti-inflammatory effects of systemic anti-tumour necrosis factor α treatment in human/murine SCID arthritis. Issue 7 (1st July 1999) - Schädlich, Hiltrud; Ermann, Jörg; Biskop, Maria; Falk, Werner; Sperling, Frauke; Jüngel, Astrid; Lehmann, Jörg; Emmrich, Frank; Sack, Ulrich
Abstract : OBJECTIVES: To evaluate in vivo the contribution of tumour necrosis factor α (TNFα) to the chimeric transfer model of human rheumatoid arthritis synovial membrane into SCID mice (hu/mu SCID arthritis), systemic anti-TNFα treatment was performed and the clinical, serological, and histopathological effects of this treatment assessed. METHODS: Animals were treated with the rat-antimouse TNFα monoclonal antibody V1q, starting on day 1 after hu/mu engraftment, twice weekly for 12 weeks. Joint swelling, serum concentrations of human and murine interleukin 6 (IL6), and serum amyloid P (SAP) were measured. Histopathological and immunohistochemical analyses of the joints were also performed at the end of treatment. RESULTS: Neutralisation of murine TNFα induced the following effects: (a) reduction of extent and duration of the acute arthritis phase, with significant reduction of joint swelling at two weeks; (b) decrease of murine SAP concentrations after the first antibody administration; and (c) increase of murine IL6 in the serum. At the end of treatment, there was a significant reduction of the inflammatory infiltration in the engrafted joints. Because of the mild degree of joint erosion, no treatment effects could be demonstrated on the destructive process. CONCLUSION: In the lymphocyte independent hu/mu SCID arthritis, anti-TNFα treatment reduces local and systemic signs of inflammation.